Reevaluating Distributional Consequences of the Transition to Market Economy in Poland: New Results from Combined Household Survey and Tax Return Data - Michał Brzeziński; Michal Myck; Mateusz Najsztub (Institute of Labor Economics (IZA), 2019)
We use Pareto imputation, survey reweighting, and microsimulation methods applied to combined household survey and tax return data to reevaluate distributional consequences of the post-socialist transition in Poland. Our approach results in the first estimates of top-corrected inequality trends for real equivalized disposable incomes over the years 1994-2015. We find that the top-corrected Gini coefficient grew by 14-26% more compared to the unadjusted survey-based estimates. This implies that over the last three decades Poland has become one of the most unequal European countries among those for which top-corrected inequality estimates exist. The highest-income earners benefited the most during the post-socialist transformation: the annual rate of income growth for the top 5% of the population exceeded 3.5%, while the median income grew by about 2.5%.
Keywords: D31; D63; C46; P36; 330; income inequality; Gini index; top income shares; tax record; survey data; Pareto distribution; Poland